Governance for development: Meeting a multi-dimensional challenge - Patkar, Vivek N. (2004)
It is unfortunate but true that despite notable achievements in variety of sectors, a feeling of under achievement runs across the Indian society. Was our Five Year Planning approach faulty or were the development efforts less ambitious, are some of the questions that form the debate on the subject. In this article it is argued that our governance efforts for development should become professional. The task is multi-dimensional and therefore requires the employment of tools that can articulate the process through meaningful participation of the citizens and thus make a difference. Transparency, accountability and responsiveness of the governance is of utmost importance. This article discusses the possibility of application of select techniques from operational science and computer technology in achieving these objectives. - Reproduced.
Keywords: Good governance